2009
DOI: 10.1016/j.jasms.2009.08.006
|View full text |Cite
|
Sign up to set email alerts
|

Tunable single-photon ionization TOF mass spectrometry using laser-produced plasma as the table-top VUV light source

Abstract: Here we report on a laser plasma-based tunable VUV photoionization time-of-flight (TOF) mass spectrometer conceived mainly to study complex gaseous mixtures. Ionizing photons at tunable vacuum UV (VUV) wavelengths are generated by a gas-target laser-produced plasma, spectrally dispersed in the range 100 -160 nm and efficiently focused onto a sample molecular beam. As a test case, we studied the exhaust gas of a four-stroke moped, a typical example of a complex gaseous mixture. Due to the VUV "soft" ionization,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
26
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 17 publications
(26 citation statements)
references
References 20 publications
0
26
0
Order By: Relevance
“…A detailed description of the experimental set-up has been reported in a previous paper [16]. However, for sake of completeness, a brief description is reported here.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…A detailed description of the experimental set-up has been reported in a previous paper [16]. However, for sake of completeness, a brief description is reported here.…”
Section: Methodsmentioning
confidence: 99%
“…4821G). The mass resolution was m/Dm % 200 at m/z = 92 by using a constant extraction field of 200 V/cm and could be increased at m/Dm % 420 at m/z = 128 (naphthalene) by using pulsed/delayed extraction fields [16].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…A schematic of the experimental apparatus is shown in Figure 1, whereas the full technical details of the experimental setup of the Na-doping are reported in. [8,[25][26][27] For clarity, only a brief description of the basic details of apparatus setup is given here. The main hardware is composed of two vacuum chambers, independently evacuated by two turbomolecular pumps (1000 l/sec) and connected to each other through a 3 mm hole.…”
Section: Experimental Methodsmentioning
confidence: 99%
“…DiPalma et al have reported on the use and characterization of this method [54][55][56][57]. They have furthermore demonstrated its use to detect IPs of products of engine exhaust, with detection sensitivities comparable to VUV synchrotrons of *1 ppmv [55].…”
Section: Species Identificationmentioning
confidence: 99%